2020
DOI: 10.1590/1984-0462/2020/38/2018313
|View full text |Cite
|
Sign up to set email alerts
|

How Can New Technologies Help Reduce Absenteeism in Pediatric Consultation?

Abstract: Objective: To identify the most effective form of contact, as a possible intervention to reduce absenteeism in consultations of children with suspected or confirmed pulmonary tuberculosis. Methods: A randomized clinical trial was conducted with prospective data collection, between March 2017 and February 2018. Patients were randomized into three groups to be reminded about the appointment: telephone contact, SMS or WhatsApp, or no intervention. A convenience sample was obtained, with a significance level of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
4
0
5
Order By: Relevance
“…Deve-se ressaltar os malefícios que os registros incorretos das marcações de consultas podem repercutir para a gestão da UBS. Isso porque impede com que os pacientes sejam contactados, o que poderia ser uma forma de diminuir o absenteísmo (Bueno et al, 2020). No caso do presente estudo, das 92 ligações bem sucedidas, 20,6% (n = 19) foram excluídas por erros de registros.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Deve-se ressaltar os malefícios que os registros incorretos das marcações de consultas podem repercutir para a gestão da UBS. Isso porque impede com que os pacientes sejam contactados, o que poderia ser uma forma de diminuir o absenteísmo (Bueno et al, 2020). No caso do presente estudo, das 92 ligações bem sucedidas, 20,6% (n = 19) foram excluídas por erros de registros.…”
Section: Resultsunclassified
“…Ainda neste motivo, destacou-se que alguns pacientes não se encontravam na cidade ou estavam comprometidos com outras atividades. Nesses casos, seria interessante fazer contato com os pacientes um dia antes para confirmar sua presença, e este contato poderia ser feito por mensageiros online, por exemplo (Bueno et al, 2020).…”
Section: Horário E Dataunclassified
“…In particular, we note a consistent role of the lead time, that is, the time span between the scheduling of the appointment and the subsequent appointment, indicating that an increase in the lead time is associated with an increase in NSB (e.g., Guzek et al., 2015). In fact, most previous survey research has frequently found that one potential explanation for this relationship might be simple forgetfulness (e.g., Bueno et al., 2020), thus applying different variations of a reminder to reduce NSB. Naturally, an alternative would be to reduce lead times.…”
Section: Analysis Synthesis and Discussionmentioning
confidence: 99%
“…Although the continuously growing body of literature on NSB has been reviewed before (e.g., Stubbs et al., 2012), most such previous attempts were neither interdisciplinary nor systematic, sometimes lacking both completeness and thoroughness (c.f., Tranfield et al., 2003). For instance, while authors have increasingly summarized the literature on NSB in healthcare subspecialties such as Endoscopy (e.g., Lam et al., 2021), Pediatric (e.g., Bueno et al., 2020) or Radiology (e.g., Mieloszyk et al., 2019), to the best of our knowledge, there as yet only exists one review synthesizing the literature on the antecedents of such behavior across such subspecialties (Dantas et al., 2018), thus providing a more holistic picture on the underlying mechanisms in the healthcare industry. However, it remains largely unclear whether these initial findings are robust across different industries, and, consequently, whether, and if so to what degree, service firms might be able to learn from each other across disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Uma forma de abordagem para o desen-volvimento dessas estratégias são ações realizadas por meio de redes sociais, tal como o WhatsApp ® , que facilitam o desenvolvimento de ações educativas em grupos mesmo na impossibilidade da reunião dos indivíduos no mesmo local e no mesmo momento [9][10][11] . Ao longo do tempo essas ferramentas têm se consolidado como uma boa estratégia de vinculação às ações de educação em saúde pelo amplo acesso de diversos seguimentos populacionais [9][10][11][12] . Esse evento parece ter se acentuado no contexto da pandemia causada pelo vírus COVID-19 que foi declarada em 2020 e exigiu isolamento social 9 .…”
Section: Efeito De Uma Ação De Aconselhamento Nutricional Com Uso De ...unclassified